Self care for nurses : small doses for wellness - May, Natalie; Cunningham, Tim, 1978-; Fontaine, Dorrie K. (Indianapolis, IN : Sigma Theta Tau International, 2023)
Self Care for Nurses will take you on a journey to explore proven self-care tactics, including over 30 wellness practices that tend to your mind; bite-sized exercises, giving you practical inspiration and food for thought in applying the latest in self-care research; helpful vignettes and guidance from nurses and wellness experts; and special challenges to help you claim the peace and balance you want in all aspects of your life.
Small doses for your happiness and health -- It's not what you think -- Burnout: sound familiar? -- Rewire your brain for resilience -- What's your mindset? -- Be a flashlight -- Pay attention -- Cultivate your appreciative practices -- Tend your emotional garden -- Choose joy and positivity -- Reframe -- Exercise gratitude -- Change your question, change your mind -- Use your vision to change your fate -- Go to your safe and happy place -- Cultivate your wisdom -- Rest -- Nourish your body and hydrate -- Evaluate your alcohol consumption -- Breathe deeply -- Move your body -- Integrate a life that works with a life that counts -- Make it a good place to work -- Take care of each other -- The pause: when a patient dies -- Mattering matters -- Put an end to bullying and incivility -- Advocate for yourself and others -- Lead from where you are.
Includes bibliographical references.
Description based on online resource; title from digital title page (viewed on December 27, 2024).
eBooks on EBSCOhost
Keywords: Nurses -- Job stress; Nursing -- Psychological aspects; Stress management; Self-care, Health; Burn out (Psychology) -- Prevention; Nurses -- Psychology; Self Care -- methods; Nurses -- psychology; Self Care; Soins infirmiers -- Aspect psychologique; Gestion du stress; Autothérapie.; Work-Related Health; HEALTH & FITNESS; MEDICAL; Nursing; Nurses -- Job stress; Nursing -- Psychological aspects; Self-care, Health; Stress management; Electronic books